Establishing a Rodent Model of Ventricular Fibrillation Cardiac Arrest With Graded Histologic and Neurologic Damage With Different Cardiac Arrest Durations. Issue 2 (August 2018) - Ettl, Florian; Magnet, Ingrid A.M.; Weihs, Wolfgang; Warenits, Alexandra-Maria; Grassmann, Daniel; Wagner, Michael; Teubenbacher, Ursula; Högler, Sandra; Sterz, Fritz; Janata, Andreas
ABSTRACT: Purpose: The aim of the study was to establish a ventricular fibrillation (VF) cardiac arrest (CA) resuscitation model with consistent neurologic and neuropathologic damage as potential therapeutic target. Methods: Prospectively randomized groups of experiments in two phases. In phase 1 four groups of male Sprague–Dawley rats (n = 5) were resuscitated after 6 min VFCA with 2 and 6 min basic life support durations (BLS) with and without adrenaline. In phase 2 the most promising group regarding return of spontaneous circulation (ROSC) and survival was compared with a group of 8 min CA. Resuscitability, neurologic deficit scores (NDS), and overall performance category (OPC) were assessed daily; histolopathology of the hippocampal CA1 region [hematoxylin and eosin- (viable neurons), Fluoro-Jade- (dying neurons), and Iba-1 immunostaining (microglial activation–semiquantitative)] on day 14. Results: Two minutes BLS and with adrenaline as most promising group of phase 1 compared with an 8 min group in phase 2 exhibited ROSC in 8 (80%) vs. 9 (82%) animals and survivors till day 14 in 7 (88%) (all OPC 1, NDS 0 ± 0) vs. 6 (67%) (5 OPC 1, 1 OPC 2, NDS 0.83 ± 2.4) animals. OPC and NDS were only significantly different at day 1 (OPC: P  = 0.035; NDS: P  = 0.003). Histopathologic results between groups were not significantly different; however, a smaller variance of extent of lesions was found in the 8 min group. Both CA durations caused graded neurologic, overall, such as histopathologic damage. Conclusions: This dynamic global ischemia model offers the possibility to evaluate further cognitive and novel neuroprotective therapy testing after CA.